2008
DOI: 10.3390/molecules13123224
|View full text |Cite
|
Sign up to set email alerts
|

A Preliminary Pharmacokinetic Study of Betulin, the Main Pentacyclic Triterpene from Extract of Outer Bark of Birch (Betulae alba cortex)

Abstract: During the last two decades triterpenes have attracted attention because of their pharmacological potential. Triterpene extract (TE) from outer bark of birch consisting mainly of betulin is able to form an oleogel which was successfully tested in the treatment of actinic keratosis. Some aspects of TE in vitro pharmacology are already known. Now we show preliminary pharmacokinetics of betulin and results of a subchronic toxicity study of TE in rats and dogs. Because of poor aqueous solubility of the TE-triterpe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
83
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 121 publications
(86 citation statements)
references
References 21 publications
2
83
0
1
Order By: Relevance
“…A 34% content in betulin was reported by Jäger et al in 2008 [18]. However, few studies have been made on the specie, Betula pendula Roth, in terms of the content of betulin/betulinic acid in the outer bark.…”
Section: Resultsmentioning
confidence: 94%
“…A 34% content in betulin was reported by Jäger et al in 2008 [18]. However, few studies have been made on the specie, Betula pendula Roth, in terms of the content of betulin/betulinic acid in the outer bark.…”
Section: Resultsmentioning
confidence: 94%
“…Under certain conditions, it is desirable to have longer application times for dressings since renewal may be associated with pain or with damage to the injured skin. Betulin, the main component of TE, appears not to be rapidly metabolized or excreted; after 4 weeks of daily subcutaneous application in dogs, a stable blood concentration was established which was only marginally influenced acutely by a further injection [26]. However, longer intervals should also be tested clinically.…”
Section: Discussionmentioning
confidence: 99%
“…Triterpenes show the potential to enhance epidermal permeability barrier recovery (Lee et al, 2006) and to stimulate wound healing (Harish, 2008) via the induction of basal cell proliferation (Jäger et al, 2008). Woelfle et al (2010) have demonstrated the influence of highly purified triterpenes from birch cork to promote keratinocyte differentiation as the main process, including the terminal differentiation to corneocytes.…”
Section: Introductionmentioning
confidence: 98%